GPU Solutions to Multi-scale Problems in Science and Engineering - Yuen, David A.; Wang, Long.; Chi, Xuebin; Johnsson, Lennart; Ge, Wei.; Shi, Yaolin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book covers the new topic of GPU computing with many applications involved, taken from diverse fields such as networking, seismology, fluid mechanics, nano-materials, data-mining , earthquakes ,mantle convection, visualization. It will show the public why GPU computing is important and easy to use. It will offer a reason why GPU computing is useful and how to implement codes in an everyday situation.
Initial-value problems associated with viscoelasticity in the geosciences -- The geophysical phenomenon of Glacial Isostatic Adjustment -- Initial Value Approach with the MOL -- Elastic and Viscoelastic Responses -- Current Numerical Methods for integrating VIP -- GPU Hardware aspects -- GPU Software aspects -- Philosophy of GPU Implementation of the MOL in VIP problems -- Code conversion versus Code implementation using CUDA or Open CL -- Examples of Postglacial Rebound -- Future Perspectives of VIP on GPU.
Keywords: Computer science; Chemistry, Physical organic; Physical geography; Electronic data processing; Materials; Computer Science; Numeric Computing; Geophysics/Geodesy.; Continuum Mechanics and Mechanics of Materials; Physical Chemistry